Ion channel molecular complexes in vascular smooth muscle - Pereira da Silva, Eric A.; Martín-Aragón Baudel, Miguel; Navedo, Manuel F.; Nieves-Cintrón, Madeline (Frontiers in Physiology, 2022)
Ion channels that influence membrane potential and intracellular calcium concentration control vascular smooth muscle excitability. Voltage-gated calcium channels (VGCC), transient receptor potential (TRP) channels, voltage (KV), and Ca2+-activated K+ (BK) channels are key regulators of vascular smooth muscle excitability and contractility. These channels are regulated by various signaling cues, including protein kinases and phosphatases. The effects of these ubiquitous signaling molecules often depend on the formation of macromolecular complexes that provide a platform for targeting and compartmentalizing signaling events to specific substrates. This manuscript summarizes our current understanding of specific molecular complexes involving VGCC, TRP, and KV and BK channels and their contribution to regulating vascular physiology.